2017
DOI: 10.1016/j.seppur.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinoptilolite supported rutile TiO2 composites: Synthesis, characterization, and photocatalytic activity on the degradation of terephthalic acid

Abstract: Clinoptilolite supported rutile TiO 2 composites were synthesized for the enhancement of its photocatalytic performance in the degradation of the aqueous terephthalic acid solution under UVC illumination by the increase in its surface area and to simplify its recovery from the treated solution after use. The XRD spectra of the composites revealed the formation of pure rutile TiO 2 on the surface of the clinoptilolite. The SEM images showed the formation of the spherical TiO 2 clusters were composed of nano fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…These observations confirm the partial loading of SnO 2 into the zeolite pore system. Such shifts have been observed in combination with other nanoparticles supported on clinoptilolites, such as TiO 2 , ZnO, SnO 2 -ZnO, SnO 2 -NiO, and CuO [14,17,30,38].…”
Section: Photocatalytic Activitymentioning
confidence: 74%
“…These observations confirm the partial loading of SnO 2 into the zeolite pore system. Such shifts have been observed in combination with other nanoparticles supported on clinoptilolites, such as TiO 2 , ZnO, SnO 2 -ZnO, SnO 2 -NiO, and CuO [14,17,30,38].…”
Section: Photocatalytic Activitymentioning
confidence: 74%
“…Photodegradation with TiO 2 as a photocatalyst has recently attracted much attention as a promising method of water purification, because TiO 2 is relatively inexpensive, photochemically stable and non-toxic and can be easily recycled on an industrial scale [18][19][20]. The anatase phase of TiO 2 has been accepted as the most photoactive TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have generally focused on the calcination temperature for the formation of the anatase phase on a support [21]. Nevertheless, increasing attention has been paid to rutile TiO 2 synthesis in the recent years due to superior properties, including thermodynamic stability and possession of chemical inertness even in acidic and basic conditions [18,20]. In general, the adsorption ability of rutile TiO 2 hardly depends on temperature (the adsorption ability of rutile TiO 2 becomes low at high temperatures).…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic activity of TiO2 for organic pollutant decomposition is mainly influenced by the crystallinity, particle size, crystal phase, and surface area of the TiO2. A study conducted by Yener et al (2017) revealed that the anatase form of TiO2, which has a small particle size and high crystallinity, is needed to obtain high photocatalytic activity. However, the presence of a certain amount of TiO2 in the rutile phase can increase photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, anatase, rutile, and brookite TiO2 nanoparticles have been successfully synthesized (Zhang et al, 2014). Zhang et al (2018) successfully made rutile and anatase TiO2 nanoparticles, whereas Yener et al (2017) successfully produced TiO2 nanoparticles in the mordenite structure.…”
Section: Introductionmentioning
confidence: 99%